2018
DOI: 10.1159/000491754
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index Categories and Attained Height in Portuguese Adults

Abstract: Objective: To analyze the associations between height and BMI categories in a Portuguese representative sample. Methods: This is a cross-sectional study with a representative sample of 32,644 Portuguese adults (52.4% females). Sociodemographic and lifestyle characteristics were obtained along with self-reported height and weight. We performed generalized linear models to assess the differences in attained height across BMI categories; analyses were adjusted for age, gender, education, family income per month, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
1
5
0
1
Order By: Relevance
“…We found that the probability of having a higher BMI decreased with being taller, and the AIC analysis showed that body height was the most important variable explaining BMI, after age and education. Similar findings were reported in the literature: A study from Portugal showed a decreasing mean height with increasing BMI categories (46) . Another study carried out in 25 diverse populations from the US, Europe and Asia showed that BMI was not independent of height and that the relationship between weight and height differed significantly between males and females (47) .…”
Section: Self-rated Health Statussupporting
confidence: 91%
“…We found that the probability of having a higher BMI decreased with being taller, and the AIC analysis showed that body height was the most important variable explaining BMI, after age and education. Similar findings were reported in the literature: A study from Portugal showed a decreasing mean height with increasing BMI categories (46) . Another study carried out in 25 diverse populations from the US, Europe and Asia showed that BMI was not independent of height and that the relationship between weight and height differed significantly between males and females (47) .…”
Section: Self-rated Health Statussupporting
confidence: 91%
“…The trends of height in the world are heterogeneous and vary according to each country's singularity. A previous Portuguese study found inverse associations between BMI categories and attained height in adults (Rosario et al, 2018a), although there are inconsistent results between height and obesity in the last decades (NCD Risk Factor Collaboration (NCD-RisC), 2016; NCD Risk Factor Collaboration (NCD-RisC), 2020). We know that fruit and vegetables are low in energy density, fat and have high water and dietary fibre content.…”
Section: Discussionmentioning
confidence: 97%
“…En lo que se refiere a la talla, un estudio realizado en Inglaterra 33 informó que la altura está inversamente asociada con el IMC en adultos, y que las mujeres altas en promedio tenían menor IMC, comparado con las mujeres bajas. En otro estudio, Rosário et al (2018) 34 analizó la asociación entre la altura y las categorías de IMC y encontró que los adultos normopeso son significativamente más altos que sus contrapartes con sobrepeso y obesos. De acuerdo a lo Tabla 1.…”
Section: Datos Antropométricos Y Sociodemográficosunclassified